2012
DOI: 10.3945/jn.111.152660
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Vitamin A Differentially Regulates Chondrocyte Growth and the Expression of Aggrecan and Matrix Metalloprotein Genes in the Femur of Neonatal Rats

Abstract: Vitamin A (VA) and its active form, retinoic acid (RA), are regulators of skeletal development. In the present study, we investigated if maternal VA intake during pregnancy and lactation, as well as direct oral supplementation of neonates with VA + RA (VARA) in early life, alters neonatal bone formation and chondrocyte gene expression. Offspring of dams fed 3 levels of VA (marginal, adequate, and supplemented) for 10 wk were studied at birth (P0) and postnatal day 7 (P7). One-half of the newborns received an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…This suggests that the vulnerable period regarding maternal diet is the period of lactation when VA is transferred in milk to the nursling pups. In recent studies, we have shown that milk total retinol is increased ∼sixfold in the dams fed VA‐supplemented diet, while plasma retinol is also significantly elevated in the pups of VA‐supplemented dams, and nearly doubled after treatment with VARA, regardless of the level of VA in the mother's diet [Zhang and Ross, 2012]. MafB expression also was increased in vivo in a similar dose‐ and time‐dependent manner by RA.…”
Section: Discussionmentioning
confidence: 82%
“…This suggests that the vulnerable period regarding maternal diet is the period of lactation when VA is transferred in milk to the nursling pups. In recent studies, we have shown that milk total retinol is increased ∼sixfold in the dams fed VA‐supplemented diet, while plasma retinol is also significantly elevated in the pups of VA‐supplemented dams, and nearly doubled after treatment with VARA, regardless of the level of VA in the mother's diet [Zhang and Ross, 2012]. MafB expression also was increased in vivo in a similar dose‐ and time‐dependent manner by RA.…”
Section: Discussionmentioning
confidence: 82%
“…Stimulation of marrow stromal cells by ATRA increases their production and secretion of macrophage colony-stimulating factor (M-CSF) and granulocyte-macrophage colony-stimulating factor (GM-CSF), of which GM-CSF has been shown to increase expression of both MZF-1 and CCN3 (Nakajima et al, 1994;Hui et al, 1995;Kimura et al, 2009). Treatment with ATRA causes hypertrophy and terminal differentiation of chondrocytes, and interestingly increases their MMP-13 expression (Oettinger and Pacifici, 1990;Iwamoto et al, 1993;Yasuhara et al, 2010;Zhang et al, 2012). Calcitriol has also been shown to enhance markers of chondrocyte differentiation and activity including BMP-7, Vitamin D receptor, and the previously mentioned FGF-23 (Sanchez and He, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…We next asked whether MafB expression in bone was affected by maternal VA status or by direct oral supplementation with VARA, a combination of VA and RA [Ross et al, 2006]. In a recent study [Zhang and Ross, 2012], we have shown that the varying the VA content of the mother's diet during pregnancy results in different levels of tissue VA in their P0 neonates: the livers of pups from VA‐marginal, VA‐adequate, and VA‐supplemented dams equaled 20 ± 2.1, 32 ± 4.2, and 121 ± 17 nmol/g tissue, respectively, all of which differed ( P < 0.05) from each other. Plasma retinol also differed significantly between P0 neonates from the VA‐supplemented mothers (1.26 ± 0.07 µM) and pups from either the VA‐marginal or VA‐adequate dams (0.81 ± 0.04 and 0.94 ± 0.02 µM).…”
Section: Resultsmentioning
confidence: 99%
“…For all pups that were supplemented directly with VARA, both liver and plasma retinol were increased significantly, but to the same extent for each maternal diet. Liver total retinol increased by approximately 400 nmol/g and plasma retinol by 2 µM as a result of direct treatment with VARA [Zhang and Ross, 2012].…”
Section: Resultsmentioning
confidence: 99%